Primary care system factors and clinical decision-making in patients that could have lung cancer - Petek, Davorina (Zdravstveno varstvo, 2022)
Introduction: Lung cancer is the leading cause of cancer death, with wide variations in national survival rates. This study compares primary care system factors and primary care practitioners’ (PCPs’) clinical decision-making for a vignette of a patient that could have lung cancer in five Balkan region countries (Slovenia, Croatia, Bulgaria, Greece, Romania). Methods: PCPs participated in an online questionnaire that asked for demographic data, practice characteristics, and information on health system factors. Participants were also asked to make clinical decisions in a vignette of a patient with possible lung cancer. Results: The survey was completed by 475 PCPs. There were significant national differences in PCPs’ direct access to investigations, particularly to advanced imaging. PCPs from Bulgaria, Greece, and Romania were more likely to organise relevant investigations. The highest specialist referral rates were in Bulgaria and Romania. PCPs in Bulgaria were less likely to have access to clinical guidelines, and PCPs from Slovenia and Croatia were more likely to have access to a cancer fast-track specialist appointment system. The PCPs’ country had a significant effect on their likelihood of investigating or referring the patient. Conclusions: There are large differences between Balkan region countries in PCPs’ levels of direct access to investigations. When faced with a vignette of a patient with the possibility of having lung cancer, their investigation and referral rates vary considerably. To reduce diagnostic delay in lung cancer, direct PCP access to advanced imaging, availability of relevant clinical guidelines, and fast-track referral systems are needed.
Keywords: osnovna nega; pljuča; rak (medicina)